Analisis Kinerja Keuangan pada Koperasi Serba Usaha di Kabupaten Buleleng - I M. SARJANA; K. BUDI SUSRUSA; DWI PUTRA DARMAWAN (Universitas Udayana, 2013)
The development of cooperation in Indonesia is very fast. It can be seen from the fact that the chosen of year 2012 as the year of cooperation. The development of a cooperation can be seen from its financial performance. From seing it, the stakeholders/the outsider party can find out how well a cooperation runs its business. The financial performance of a cooperation can be judged from 5 aspects. They are : capital aspect, the quality of productive active, management aspect. Rentability aspect and liquidity aspect, according to Peraturan Koperasi Serba Usaha (the rule of multi- business cooperation) which was issued by the government through Kep Men Kop no 129 year 2002. The objective of this research is to find out how well the cooperation runs its activities, based on the rule issued by the government. And also to find out the influence of financial performance such as : solvability ratio (debt to asset ratio and debt to equity ratio), activity ratio (receivable turnover and cash turnover). Rentability ratio (earning), liquidity ratio (current ratio) toward the ability of cooperation in gaining the profit. This research is an explainatory research. The data collecting is done by taking 11 samples from 152 multy-businesses cooperation emerged in Buleleng regency. By using persuasive random sampling method, from 11 samples and their financial report: Balance sheet and lost and profit report. The instrument of data collecting is documentary study by studying the existing data from until 2012. From the result of analysis of financial ratio comparing with the standard pointed out in Kep Men no 129, year 2002, it can be found out that the average of current ratio and debt to equity ratio can be categorized as very efficient. The economy rentability and cash turn over are categorized as effisient enough, and debt to asset ratio and receivable turnover are categorized as less effisient. The financial ratio has significant influence simultaneously towards economy rentability, meanwhile, partially, it is only debt to asset ratio which has significant influence towards the rentability. Meanwhile the other four factors (aspects) don’t has significant influence. The analysis of this research is based on the result of t-test and F test done during the research.